Building resilience through integrated assistance: Evidence from the Democratic Republic of the Congo - Baoubadi, Atozou; d’Errico, Marco; Ulimwengu, John M. (Open University of Tanzania, 2024)
Despite growing investment in resilience-building programs in conflict zones, limited empirical evidence exists on the effectiveness of integrated interventions in such contexts. This study examines the impact of a comprehensive resilience-building program in North Kivu, Democratic Republic of the Congo (2017-2019), focusing on community infrastructure, farmer associations, and land access. Using propensity score matching and difference-in-differences analysis of primary panel data from 1,643 households, our research reveals that integrated interventions significantly improved households' resilience capacity, primarily through enhanced market access and strengthened collective marketing systems. The program yielded a statistically significant positive impact on beneficiaries' access to land and participation in community associations, though impacts on agricultural production and food security were limited. These findings highlight the importance of context-specific, multifaceted approaches in enhancing resilience in areas facing protracted crises, particularly emphasizing market access and social cohesion. Our results provide valuable empirical evidence for policymakers and development practitioners, suggesting that resilience-building in conflict zones requires sustained, locally-adapted interventions that prioritize market linkages and community networks alongside traditional agricultural support.